Integrating the Traditional Games into Early Childhood Programs: Effects on Gross Motoric Skill Enhancement Using a One-Group Pretest–Posttest Design - Wulandini S, Putri; Kartika, Imelda Rahmayunia (Universitas Muhammadiyah Surakarta, 2026)
Gross motoric skill development in children is a basic component of children’s growth and their physical functional movement. This study was conducted using pilot quantitative study that evaluated the effectiveness of traditional Riau games in improving gross motoric skills, specifically balance, speed, and agility, among pre-school children. This study used a non-randomized, single-group pretest–posttest design without a control group, conducted on 50 participants. Gross motoric performance was assessed pre and post intervention by using an instrument of TGMD (Test of Gross Motoric Development). Data were analyzed using paired sample t-tests, with effect sizes calculated to estimate strong effects taken from this study. The results indicated statistically significant improvements in balance, speed, and agility following the intervention (p < 0.001), with a very large effect size (Cohen’s d = 2.39 ≥ 0.80). These findings suggest that traditional Riau games may represent a culturally appropriate and effective strategy for enhancing children’s gross motoric skills. Nevertheless, the absence of a comparator group and the pilot nature of the study warrant cautious interpretation, and further controlled trials are recommended to confirm these results.